Pemberdayaan Masyarakat Desa Dalam Pembangunan Desa Wisata Melalui Metode Serap Aspirasi Masyarakat - Husein Abdurahman; Sarwani; Angga Ardiyanto; Budi Rahman; Miftahul Jannah; Nur Laeliana; Rinaldi Juliansyah; Rizky Annisa (Journal of Empowerment and Community Service (JECSR), 2021)
Sungai Langsat Village has beautiful natural conditions and has tourist attraction and potential which if developed provides opportunities for this village to become a tourist village. The methodology used in carrying out this aspiration absorption activity is the Participatory Rural Appraisal (PRA) method. The result of this program is that the people of Sungai Langsat village, who initially did not know what a tourist village was, became aware of it and the response given by the village community regarding building a tourist village was also quite good. It is hoped that the village government can increase the participation of the village community based on the results of the study conducted, and for the community it is hoped that it will be more active in participating in village development, especially in village tourism planning which at the same time moves and grows the economy of rural communities